Finite Element Method of Normal Reinforced Concrete Slab under Contact Explosion - ปราปต์บุณฑริก คณาธิป; Limpaninlachat, Pornpen; Pansuk, Withit (การประชุมวิศวกรรมโยธาแห่งชาติ ครั้งที่ 28, 2023)
Blast load is a special and specific situation that rarely occurs in structural engineering, but it can cause severe damage to the structure and user due to the high energy dissipation in both tension and compression. The experiment under blast conditions is difficult to conduct because of safety and taken high cost. Therefore, the Finite Element Method (FEM) is the effective method to investigate the blast load behaviors. This research aims to study the FEM analysis to create a numerical simulation of Normal Reinforced Concrete (NRC) slabs under blast conditions. The experimental results from the previous study were employed to validate the numerical simulation model with FEM software. The NRC slabs in 2000mm x 1000mm x 75mm of dimension under 1 lb and 2 lbs of TNT at 500 mm of standoff distance were used as the validated specimens. To model the structure under blast loads, additional properties regarding high strain rate condition were required, such as erosion. The validation between results from models and experiments such as maximum deflection and overpressure regarding the blasting of normal RC slabs with different blast loads were examined. According to the numerical results, with increase of the explosive charge weight from 1 lb to 2 lbs resulted in the more damage on slab surface and higher maximum deflection.